UPAYA ORANG TUA MENGATASI KEBERLANJUTAN PENDIDIKAN ANAK DI DESA PIAWAS KECAMATAN BELIMBING HULU - Bonifasius Aleng; Sulistyarini Sulistyarini; Supriadi Supriadi (Universitas Tanjungpura, 2019)
AbstractOvercoming the Sustainability of Children's Education in Piawas Village, Belimbing Hulu Subdistrict, Melawi Regency. The method used was descriptive method. The form of research is a case study.The results of the study are as follows: 1) Preventive measures taken by parents to overcome the Sustainability of Child Education in Piawas Village in Belimbing Hulu Subdistrict, Melawi Regency The income of parents in Piawas Village, Belimbing Hulu Subdistrict, Melawi Regency, in this case parents can pay special attention to their children such as giving advice to children related to the impact of not attending school, as well as providing motivation to children to continue their education, even though in difficult circumstances, still maintain more communication in order to understand the condition of the child. 3) Repressive efforts by parents to overcome the Sustainability of Children's Education in Piawas Village, Belimbing Hulu Subdistrict, Melawi District. What kind of development is for children who drop out of school. Efforts in the form of being given advice to children with the aim that the condition is back in conducive again and the child does not repeat his actions not to continue his education. Keyword :Parents' Efforts, Overcoming the Sustainability of Children's Education